(untitled) (Bangladesh Veterinarian, 2016)
To determine the factors affecting onset of postpartum ovarian cyclicity (PPOC) milk progesterone concentrations were measured in 84 cows. About 30% showed cyclicity within 120 days of parturition. Intensively managed cows started cyclicity earlier (P>0.05) than extensively managed animals. Holstein-Friesian crossbred cows started ovarian cyclicity earlier (80.2 ± 17.5 days) with higher proportion (37.9%) than local zebu cows (84.8 ± 21.0 days) and about 13.3%, respectively (P>0.05). The cows yielding 4-12 kg milk/day required 73.5 ± 10.0 days to start ovarian function earlier than those producing 1-2 kg/day (84.8 ± 21.0 days) (P>0.05). Cows with lower (<200 kg) and higher (>300 kg) body weights started ovarian activity by 81.6 ± 16.6 and 76.3 ± 17.4 days, respectively (P>0.05). Cows with lower body weight showed PPOC at lower rate (5.2%) than those of medium (38.3%) and higher body weight (33.3%) (P<0.05). The delayed onset of PPOC prolonged the calving interval. Bangl. vet. 2015. Vol. 32, No. 1, 27-34